(untitled) (Journal of actual problems of jurisprudence, 2018)
The article is devoted to analysis of the main direction of activity of the President of Kazakhstan as a guarantor of the fundamental rights and freedoms of citizens of Kazakhstan, the definition of the specificity of this activity. The author reveals features of the President’s activities to protect socially vulnerable groups of the population. President of Kazakhstan is an important element of the institutional component of constitutionalism in Kazakhstan. RK Constitution provides that the President of the Republic of Kazakhstan is the guarantor of the rights and freedoms of citizens. In the Address of the President RK great importance given to the development of the social sector. Key words: President of Kazakhstan, Presidential Address to the people of Kazakhstan, the rights and freedoms of citizens of Kazakhstan, the mechanism of protection of the rights and freedoms of citizens.